2020
DOI: 10.1111/jcpe.13387
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric soft tissue alterations in the early healing phase after peri‐ implant soft tissue contour augmentation with a porcine collagen matrix versus the autologous connective tissue graft: A controlled clinical trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 32 publications
(71 reference statements)
1
43
0
1
Order By: Relevance
“…The authors concluded that in both cases there was an increase in the soft tissue thickness, but higher values were noted in the group where CTG was used [31]. The CTG regarded as the gold standard has also demonstrated greater efficiency in the early healing phase after surgery [32]. Similar data were obtained by other authors who carried out a comparative analysis of the use of CTG and collagen matrixes to increase the soft tissue volume [30,33].…”
Section: Resultssupporting
confidence: 57%
“…The authors concluded that in both cases there was an increase in the soft tissue thickness, but higher values were noted in the group where CTG was used [31]. The CTG regarded as the gold standard has also demonstrated greater efficiency in the early healing phase after surgery [32]. Similar data were obtained by other authors who carried out a comparative analysis of the use of CTG and collagen matrixes to increase the soft tissue volume [30,33].…”
Section: Resultssupporting
confidence: 57%
“…Nine articles were excluded after careful reading, since they did not meet the eligibility criteria. Finally, 19 studies [ 12 , 16 , 19 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] were included in the systematic review (SR) and one of them was excluded for the quantitative analysis, so the meta-analysis is based on 18 articles [ 12 , 16 , 19 , 27 , 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. The reasons for exclusion are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Varied applications for soft tissue augmentation were described in the included studies: 12 articles in relation to implant sites [ 12 , 16 , 19 , 29 , 31 , 32 , 34 , 37 , 38 , 39 , 42 , 43 ] and 7 concerning teeth [ 27 , 28 , 33 , 35 , 36 , 40 , 41 ]. All the included studies were RCTs except for three CCTs [ 31 , 37 , 42 ], but all of them included at least two parallel arms, the use of CTG versus CM. The different therapeutic options used for soft tissue augmentation found in the included studies are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations